Impacts of Toothache on Daily Activities of Children Aged 5 to 9 Years in Kerman, Iran - Mahsa Kalantary; Maryam Alsadat Hashemipour; Mahbobeh Ahmadbeighi; Leila Shafie Bafti; Amir Reza Gandjalikhan Nassab (Pesquisa Brasileira em Odontopediatria e Clínica Integrada, 2022)
Objective: To investigate the impacts of toothache on the daily activities of children aged 5 to 9 years. Material and Methods: A cross-sectional analytical study was conducted among 465 children (220 boys and 245 girls) aged between 5-9 years, using the Child Dental Pain Questionnaire (Child-DPQ), in the city of Kerman. They were categorized into two groups based on the clinical status: (1) untreated dental caries and (2) no dental caries or treated dental caries. For data analysis, the Chi-square, Mann-Whitney test, multiple logistic regressions, Spearman’s correlation coefficient and t-test were used. Results: Regarding the severity of pain, about 28.3% reported mild pain, 30.1% moderate pain, and 21.9% very severe pain. The prevalence of reported dental pain increased by increasing the number of reported dental visits and more strongly among those having dmft>1. Toothache in children caused to stop eating (73.3%) and to sleep (63.8.1%) and provoked a dental visit in more than 40%. Conclusion: The toothache stopped many children eating and sleeping and provoked a dental visit in more than 40%. Among the children under study, 55.9% had to miss school.